Warming alters the responses to light availability in seedlings from contrasting provenances of the mid-tolerant beech Nothofagus pumilio - Aparicio, Alejandro Gabriel; Torres, Ana Delia; Pastorino, Mario Juan (Elsevier, 2025)
The survival and growth of shade-tolerant tree seedlings depend strongly on their ability to respond to varying light conditions in both natural and managed systems. Rising temperatures may constrain these light-driven responses, posing challenges for forest management and afforestation efforts. This study examines how warming affects light responses in Nothofagus pumilio seedlings, using a multi-site genetic trial. Seedlings from four environmentally contrasting provenances were subjected to three thermal regimes, simulating future climates, and three light availability levels during their first post-planting year. Warming significantly reduced the magnitude and amplitude of reaction of growth responses, particularly biomass allocation and crown architecture traits. For example, the mean total dry weight at the coolest site (TDW= 7.43 g) increased by 56 % from low to mid-light availability, compared to only 3 % at the warmest site (TDW= 5.62 g). Moreover, while the average length of the annual shoot (l.AS) exhibited a 26 % increase at the coolest site (l.AS= 15.4 cm), at the warmest site (l.AS= 9.1 cm) it decreased by 20 % from low to mid-light levels. Marked genetic differences were observed between northern and southern provenances, especially in leaf morpho-physiological traits. These findings highlight the need for carefully targeted site selection for afforestation, favoring stable light conditions near new optimum. Nurse vegetation management and other protective measures may become increasingly necessary. This research provides critical insights for the development of seed orchards and transfer zones in N. pumilio, informing conservation and utilization strategies to enhance its resilience facing climate change.